Interactive information retrieval in digital environments - Xie, Iris, 1965- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book includes the integration of existing frameworks on user-oriented information retrieval systems across multiple disciplines; the comprehensive review of empirical studies of interactive information retrieval systems for different types of users, tasks, and subtasks; and the discussion of how to evaluate interactive information retrieval systems"--Provided by publisher.